PENGGUNAAN MEDIA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII SMP NEGERI 1 SERAM BARAT TERHADAP MATERI BANGUN RUANG - Oktovianus Mandaku (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2014)
Matematic learning in school is not only prepares students to be able to apply mathematics knowledge in their life, but also to make them how to have logical and critical thinking and how to innovate Matematic learning success, if the teachers can make the student’s behavior change. Although using media is very good but in fact the convension has not success teached the students. This problem make the writer to make the research with topic “Using media to motivate students to increase their studying achievement in eight grade students of SMP Negeri 1 Seram Barat into geometry subject.This research in order to increase studying achievement and also to know students responding to understand the geometry. Class Action research is really suit research for the Teacher’s job and function. According to the result of the last action test, so the success get 90,32 %, and unluck got 09,68 %Keywords : Media, achievement and geometry